2012
DOI: 10.1111/j.1538-7836.2012.04674.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in thrombotic thrombocytopenic purpura

Abstract: To cite this article: Ré ti M, Farkas P, Csuka D, Rá zsó K, Schlammadinger Á , Udvardy ML, Madá ch K, Domjá n G, Bereczki C, Reusz GS, Szabó AJ, Prohá szka Z. Complement activation in thrombotic thrombocytopenic purpura. J Thromb Haemost 2012; 10: 791-8.Summary. Background: Ultra-large von Willebrand factor and deficiency of its cleaving protease are important factors in the events leading to thrombotic microangiopathy; however, the mechanisms involved are only partly understood. Whereas pathological activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 29 publications
(33 reference statements)
4
105
1
2
Order By: Relevance
“…Previously our group reported on the presence of complement activation in patients with acute TTP [10] an observation recently confirmed in an independent cohort [11]. Our data indicated that activation of the classical/lectin and alternative pathways that lead to the activation of the terminal pathway was present in TTP.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Previously our group reported on the presence of complement activation in patients with acute TTP [10] an observation recently confirmed in an independent cohort [11]. Our data indicated that activation of the classical/lectin and alternative pathways that lead to the activation of the terminal pathway was present in TTP.…”
Section: Introductionsupporting
confidence: 82%
“…Previously we [10] and others [11] documented the activation of the classical/lectin, the alternative and the terminal pathways of complement in TTP. Our current results indicate the association between PMNE and C3 activation (C3a), and the presence of NETs may be a potential link between these factors.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…While our results did not find a statistically significant increase in iC3b and sC5b-9 complexes in TTP patients when compared with healthy controls, other studies have demonstrated the increased levels of C3a and sC5b-9 during acute TTP. 45 Moreover, the increased levels of Bb, C3a, and C5a, and sC5b-9 appear to correlate with a worse outcome in TTP. 46 We did not find an association between any of these markers we measured and the relapse and mortality rate in our cohort of patients.…”
Section: Discussionmentioning
confidence: 95%